Shared Margins : an Ethnography with Writers in Alexandria after the Revolution - Schielke, Joska Samuli; Shehata, Mukhtar Saad (ZMO-Studien, 2021)
Shared Margins tells of writers, writing, and literary milieus in Alexandria, Egypt's second city. It de-centres cosmopolitan avant-gardes and secular-revolutionary aesthetics that have been intensively documented and studied since 2011. Instead, it offers a fieldwork-based account of various milieus and styles, and their common grounds and lines of division. Structured in two parts, Shared Margins gives an account of literature as a social practice embedded in milieus that at once enable and limit literary imagination, and of a life-worldly experience of plurality in absence of pluralism that marks literary engagements with the intimate and social realities of Alexandria after 2011. Literary writing, this book argues, has marginality as an at once enabling and limiting condition. It provides shared spaces of imaginary excess that may go beyond the taken-for-granted of a societal milieu, and yet are never unlimited. Literary imagination is part and parcel of such social conflicts and transformations, its role being neither one of resistance against power nor of guidance towards norms, but rather one of open-ended complicity.